Cultivating a culture of post- COVID-19 prevention : understanding knowledge, awareness and practices of COVID-19 in Sarawak - Abang Azlan, Mohamad; Lo, May Chiun; Wan Hashim, Wan Ibrahim; Ramayah, T.; Chin, Ying Sin (Emerald Publishing Limited, 2024)
Purpose – This study aims to examine the relationship between public knowledge, awareness and attitudes towards post-COVID-19 infection prevention in Sarawak. At present, Sarawak is in the post-pandemic stage, marked by a gradual return to normalcy, albeit with some persistent changes caused by the pandemic. Design/methodology/approach – Data were collected from various geographic areas in Sarawak through a Google Form link and QR code during a cross-sectional study, resulting in the acquisition of 1,128 responses. Data analysis was performed using SPSS 28.0 and WarpPLS 8.0. Findings – The result revealed that out of five hypotheses, four were found to be supported, indicating a positive relationship between public knowledge, awareness and attitudes towards COVID-19 infection prevention. However, an unsupported relationship was found between public awareness and infection prevention practices. Research limitations/implications – This study is limited to the Malaysian population and has a cross-sectional design, affecting generalizability. It is recommended that future research complete an in-depth study of the knowledge, awareness and practices of COVID-19 using other data collection techniques. Practical implications – Public health and policymakers can use the study to implement effective communication strategies and prioritize digitalization for economic recovery. It highlights the importance of preventive measures and the public’s role in managing future pandemics. Originality/value – The originality of this research can be drawn from key findings that indicate that people overall gained knowledge on the prevention measures during the post-COVID-19 pandemic, and the accuracy of the information significantly impacts public knowledge, awareness and practices of COVID-19 infection prevention.